SUMBER-SUMBER ILMU PENGETAHUAN DALAM PERSPEKTIF ISLAM DAN BARAT - Nawazir, Safrudin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this paper is to find out the sources of knowledge in Islamic and Western perspectives. This research uses library research. The results of the study show that: sources of knowledge from Islam come from the AlQur'an, Assunnah / hadith of the Prophet Muhammad SAW, Reason, Revelation, inspiration, five senses, experience, intuition etc. In Western epistemology, there are three ways to acquire knowledge: First, the rationalist approach. An understanding that knowledge occurs because of material given to the five senses and the mind which is processed by